Evaluation of Retinal Pigment Epithelial Cell Cytotoxicity of Recombinant Tissue Plasminogen Activator Using Human-Induced Pluripotent Stem Cells - Hiroyuki Kamao; Atsushi Miki; Junichi Kiryu (Journal of Ophthalmology)
Purpose. The evaluation of drug-induced cytotoxicity is of great importance for the clinical application of pharmaceutical products, and human-induced pluripotent stem cells (hiPSCs) have received considerable scrutiny as a cell source for in vitro cytotoxicity testing. The aim of this study is to validate the concept of cytotoxicity testing using hiPSC-derived retinal pigment epithelium (hiPSC-RPE) by comparing the responsiveness of human fetal RPE (hfRPE) and human RPE cell line (ARPE19) to recombinant tissue plasminogen activator (rtPA). Methods. HfRPE, two types of hiPSC-RPE, and ARPE19 were cultured in media with or without rtPA. A lactate dehydrogenase release assay was performed to investigate the dose- and time-dependent effects of rtPA on cell death. RPE function was evaluated by measuring the secretion of pigment epithelium-derived factor (PEDF) and vascular endothelial growth factor (VEGF) and RPE-specific gene expression. Results. Rates of cell damage in hfRPE and both hiPS-RPE were increased by rtPA supplementation (2000 and 4000 μg/ml) for 1 hour, whereas ARPE19 cell damage was increased by supplementation with rtPA at concentrations higher than 50 μg/ml. Although 100 μg/ml rtPA for 24 hours did not affect RPE cell function, sustained rtPA exposure induced prolonged cytotoxic effects in hfRPE and two hiPSC-RPE, but not ARPE19. Conclusion. The responsiveness of hiPSC-RPE to rtPA is similar to that of hfRPE in terms of cell death and cell function. Thus, hiPSC-RPE is a valuable cell source for in vitro cytotoxicity testing.